Formation of large 2D arrays of shape-controlled colloidal nanoparticles at variable interparticle distances - Ullrich, Simon; Scheeler, Sebastian Paul; Pacholski, Claudia; Spatz, Joachim P.; Kudera, Stefan (Particle & particle systems characterization, 2013)
A method for the production of homogeneous layers of nanoparticles of arbitrary shape is presented. The method relies on a ligand exchange with a functionalized polymer and a subsequent self-assembly of a thin film on the substrates. The interparticle distances in the layer can be adjusted by the length of the polymer. In the case of spherical particles, the approach yields quasi-hexagonal structures; in the case of anisotropic particles, the minimum distance between adjacent particles is controlled. Regular arrangements of the nanoparticles covering areas of several square centimeters are achieved.
First published: 07 November 2012
Gesehen am 17.02.2022